Khảo sát ý kiến sinh viên Trường Đại học Mỏ - Địa chất về bài tập lớn học phần “Sức bền vật liệu”: Cơ sở định hướng cải tiến hệ thống đánh giá quá trình trong đào tạo kĩ sư - Trần, Mạnh Tiến; Đặng Văn Thái, Đặng Văn Thái; Đỗ Ngọc Tú, Đỗ Ngọc Tú (Tạp chí Giáo dục, 2026)
In the context of higher education reform toward competency-based education, this study aims to evaluate the role of the Strength of Materials course project in formative assessment for engineering students. The study employed a survey method, descriptive statistics, and analytical-synthetic approaches based on 382 valid student responses. The findings indicate that most students perceived the course project as necessary and effective in developing professional knowledge, engineering thinking, self-directed learning, and problem-solving skills. However, several limitations were identified, including insufficient disciplinary differentiation, inappropriate levels of difficulty, limited practical relevance, and issues related to plagiarism. Based on these findings, the study proposes several measures to improve the course project, including differentiating task complexity, adapting content to specific disciplines, enhancing practical relevance, standardizing instructional guidelines, developing digital learning resources, and revising assessment rubrics to improve the effectiveness of formative assessment in engineering education. The findings provide a practical basis for improving the formative assessment system in competency-based engineering education.